Tailoring magnetic properties of FeCoBi nanowires through controlled synthesis and post-deposition treatments - Shaghayegh Afshar; Mojgan Najafi; Akbar Heidarpour (Results in Physics)
This study presents the fabrication, crystalline identification, and magnetic characterization of iron-cobalt-bismuth (FeCoBi) nanowires, with a focus on the effects of Bi concentration, annealing, pH, and deposition frequency. FeCoBi nanowires were synthesized using template-assisted electrodeposition with varying concentrations of bismuth nitrate in the electrolyte. FeCoBi nanowires with varying Bi contents (0–10.36 wt%) were fabricated using the AC electrodeposition method within an anodic aluminum oxide (AAO) template. The results indicate that the crystal structure of FeCoBi nanowires remains bcc with a peak at 45.9° for Bi content up to 6.8 wt%, but transitions to an amorphous structure as the Bi content increases further. It was observed that the coercivity of all nanowires improved after annealing. The most significant increase was found in FeCoBi nanowires with 9 wt% Bi (0.008 M Bi+3), where the coercivity rose from 1345 Oe before annealing to 2647 Oe after annealing at 500 °C. Additionally, altering the pH of the electrodeposition solution (0.008 M Bi+3) enhanced the coercivity of FeCoBi nanowires from 1345 Oe at pH 3 to 1887 Oe at pH 6. The crystal structure of the nanowires transitioned from amorphous at pH 3 to a bcc structure at pH 6. Furthermore, increasing the electrodeposition frequency led to higher coercivity due to a reduced deposition rate and improved crystallinity. For FeCoBi nanowires (0.008 M Bi+3), the coercivity increased from 1108 Oe at 100 Hz to 1677 Oe at 800 Hz. Post-annealing of nanowires fabricated at different frequencies resulted in enhanced coercivity for all samples, with a notable 92 % improvement in coercivity observed for nanowires deposited at 600 Hz. The results demonstrate the potential of FeCoBi nanowires for applications in high-density magnetic storage and spintronic devices, where tailored magnetic properties are crucial for optimal performance.